2020
DOI: 10.1093/mnras/staa724
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric compositions and observability of nitrogen-dominated ultra-short-period super-Earths

Abstract: We explore the chemistry and observability of nitrogen dominated atmospheres for ultra-short-period super-Earths. We base the assumption, that super-Earths could have nitrogen filled atmospheres, on observations of 55 Cnc e that favour a scenario with a high-mean-molecular-weight atmosphere. We take Titan's elemental budget as our starting point and using chemical kinetics compute a large range of possible compositions for a hot super-Earth. We use analytical temperature profiles and explore a parameter space … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 90 publications
0
48
0
Order By: Relevance
“…The atmospheric composition of this planet is currently still debated based on tentative atmospheric HCN observations with the Hubble Space Telescope. HCN would imply a reducing, N 2 -dominated atmosphere instead of an oxidizing atmosphere as assumed in this study (Tsiaras et al, 2016;Hammond and Pierrehumbert, 2017;Zilinskas et al, 2020). Future observations with JWST or the ELT will target 55 Cancri e as an example to study the evolution of magma ocean planets and the influence of these magma oceans on the atmosphere.…”
Section: Discussionmentioning
confidence: 86%
“…The atmospheric composition of this planet is currently still debated based on tentative atmospheric HCN observations with the Hubble Space Telescope. HCN would imply a reducing, N 2 -dominated atmosphere instead of an oxidizing atmosphere as assumed in this study (Tsiaras et al, 2016;Hammond and Pierrehumbert, 2017;Zilinskas et al, 2020). Future observations with JWST or the ELT will target 55 Cancri e as an example to study the evolution of magma ocean planets and the influence of these magma oceans on the atmosphere.…”
Section: Discussionmentioning
confidence: 86%
“…This point was discussed in Angelo & Hu (2017), who suggested that an N 2 -dominated atmosphere would be consistent with the Spitzer data. The possible composition of a nitrogen-dominated atmosphere and the observability of spectral features are explored in Miguel (2019) and Zilinskas et al (2020). However, such a thick atmosphere would be unlikely to change substantially on yearlong timescales.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if HRSEs have remaining volatile elements such as H, C, N, S and Cl, they likely have atmospheres composed mainly of H 2 O and/or CO 2 with rocky vapours such as Na and SiO [10,129]. Or by HCN in case of N-dominated atmospheres [95,171] Generally, we call the former case a mineral atmosphere and the latter case a steam atmosphere. Thus, detection of rocky vapour would provide a definitive piece of evidence for HRSEs and their surface composition, including indications of their deeper structure.…”
Section: Constraints On Magma Composition Of Hot Rocky Super-earths From Atmospheric Measurementsmentioning
confidence: 99%